Deoxynivalenol and pigs: review of harmful effect of Mycotoxin on swine health - Izabela Malczak; Anna Gajda; Piotr Jedziniak (Porcine Health Management)
Abstract Mycotoxins are compounds produced by certain types of fungi, and the mycotoxin one of the most most frequently found in the tested cereal samples is deoxynivalenol (DON), naturally-occurring mycotoxin produced by Fusarium spp. An animal sensitive to the effects of this mycotoxin is the pig due to the diet containing primarily cereals and the structure of a digestive system, which causes DON to be quickly absorbed unchanged into the bloodstream and partially metabolized in the liver. An important aspect when considering the toxicity of DON is the occurrence of its modified forms, which can be transformed into DON in the digestive system. The toxic effect of DON can also be caused by other mycotoxins which co-occur in cereals. The toxic effect of DON on the body of pigs was observed mainly in the digestive, immune, and reproductive systems. The noticeable of DON’s toxic effects depends on the exposure time, route of administration and mycotoxin concentration. The changes are mainly caused by impaired gene expression, inhibiting protein synthesis or the effect of DON on pathways in pigs’ bodies. The negative impact of DON on the health of pigs may lead to reduced weight gain, poor health, and increased susceptibility to infections and reproductive disorders. There have also been many methods of DON elimination from cereals, but their efficiency is insufficient.